The schooling of children of inmigrants: contextual effects on the educational attainment of the second generation - Portes, Alejandro; Hao, Lingxin (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
We supplement earlier published findings on the academic achievement of the immigrant second generation with an analysis of school contextual effects based on the same large data set used by the best-known prior analyses, the Children of Immigrants Longitudinal Study (CILS). A hierarchical model of contextual and individual-level effects on academic achievement and school attrition reveals patterns that reproduce those found in national student surveys, but also others that are unique to the second generation. Among the latter: the resilient negative effect of length of U.S. residence on achievement across school contexts and the fact that strong effects of national origin on grades are attenuated in schools with high proportions of co-ethnics. Mexican-origin students display significant disadvantages in achievement and retention that are generally compounded, not alleviated, by the schools that they attend. A theoretical explanation of this pattern is advanced and its practical implications discussed.
Keywords: 2.nd generation; Scholing; Educational achievement; U.S.A